Effect of Food Review in Zomato Applications as eWOM on Customer Purchase Intention - Zunvindri, Zunvindri; Natasha, Natasha; Abdurrachman, Edi (Unisia, 2021)
Eating is no longer just to meet the needs, but also become an activity of socializing. With the increasing number of places to eat in Indonesia, encourage people to find a recommendation for a place to eat before deciding to try the food at the eating place. But, when it came to the internet and smartphone, people can easily get digital recommendation information, in the form of reviews provided by those who like to share their dining experiences (foodies). This digital recommendation is then called Electronic Word of Mouth. However, the review given digitally or online has its drawbacks, less objective, ending with a disappointing experience. This research objective is to discuss the effect of using Zomato on users' intentions to purchase or try food or restaurants. Descriptive quantitative approach and complete technique of survey data using questionnaire would be executed. Data analysis in this research is descriptive statistic and regression. Results obtained are information quality, information credibility, need of information, and attitude toward information have positive influence on information adoption. Moreover, information adoption also has positive influence on customer purchase intention. The conclusion from this study shows the variables that are interconnected and affect each other.